2014
DOI: 10.1177/0004563214557568
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in variegate porphyria: a case report and literature review

Abstract: Variegate porphyria is an autosomal dominant acute hepatic porphyria characterized by photosensitivity and acute neurovisceral attacks. Hepatocellular carcinoma has been described as a potential complication of variegate porphyria in case reports. We report a case of a 48-year-old woman who was diagnosed with hepatocellular carcinoma following a brief history of right upper quadrant pain which was preceded by a few months of blistering lesions in sun-exposed areas. She was biochemically diagnosed with variegat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A previous study reported a young VP case with epilepsy, mental retardation and premature adrenarche symptoms, but death occurred later [ 15 ]. Hepatocellular carcinoma in VP has been described in at least eight cases with VP, indicating the risk of cancer in these patients [ 19 ]. All of these data emphasize that there are various skin and neurological symptoms in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a young VP case with epilepsy, mental retardation and premature adrenarche symptoms, but death occurred later [ 15 ]. Hepatocellular carcinoma in VP has been described in at least eight cases with VP, indicating the risk of cancer in these patients [ 19 ]. All of these data emphasize that there are various skin and neurological symptoms in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Acute hepatic porphyrias which include 3 autosomal dominant disorders: Acute intermittent porphyria (AIP), variegate porphyria (VP) and hereditary coproporphyria (HCP) has also been considered as a cause of non-cirrhotic HCC[66]. Overproduction of aminolevulinic acid and/or porphobilinogen overproduction and excretion has been implicated as a cause of hepatic carcinogenesis in AIP, but the mechanism is poorly understood in VP and HCP[67].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Evidence linking HCC to VP is insufficient and is related to a small number of published case reports and some individuals identified in cohort studies [36][37]. The cohort studies gave frequencies ranging from 1.3% to 5.4% [38].…”
Section: Plc In Pvmentioning
confidence: 99%